Evaluation of a Modified Manual Restraint Test for Estimating Fearfulness in Laying Hens - Fukano, Natsuki; Wada, Natsuho; Oka, Takao; Bungo , Takashi (International Journal of Poultry Science, 2015)
The aim of the present study was to evaluate effect of a new manual restraint test for the detection of fearfulness on the blood parameters in hens. Each chicken was held in an underarm with mild pressure, whereas the other hand was used to restrain the legs. Thereafter, latencies to the first struggle and frequencies of struggling were recorded for 5 min. At the end of the test, the blood samples were collected. At one week after the test, their bloods were collected again as control. Median of latency (sec.) or frequency (number) of struggling in laying hens was 116.0 and 4.5, respectively. No significant differences were detected in the levels of glucose and FFA by manual restraint while the level of corticosterone just after the test was higher than that at one week after the test. These findings demonstrate that the newly developed restraint test is useful for detecting fearfulness in chickens.